A Review of Trajectories for External Cranial Ventricular Access (Nepal Journal of Neuroscience, 2021)
In literature there are many access points that can be performed either as free hand, with navigation or with help of localizing devices. A thorough knowledge of these access points, their history, external landmarks, trajectories and indications will help to manage all cases requiring ventricular drainage. This article discusses only the points for external ventricular access for the ventricles highlighting with original diagrams where available, the different access sites. Kocher’s / Tillman’s / Neisser and Pollack, Von Bergman/ Kaufman’s, Tubbs’/ Navarro/ Wilson point, Bohl's, Sanchez’s points, Frazier’s, Dandy’s and Keen’s points are discussed along with original drawings where available.